2016
DOI: 10.1186/s40661-016-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-sparing management in cervical cancer: balancing oncologic outcomes with reproductive success

Abstract: BackgroundCervical cancer is the fourth most common cancer among women worldwide, many of who are still within their reproductive lifespan. Advances in screening and treatment have increased the 5-year survival for early stage disease to over 90 % in developed countries. The focus is now shifting to reducing morbidity and improving fertility outcomes for cervical cancer patients. Radical trachelectomy with lymph node assessment became the standard of care for selected women with lesions <2 cm who desire fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 128 publications
5
40
0
6
Order By: Relevance
“…In agreement with Bradbury et al we found significant correlation of OS with lymph node metastasis but not extrauterine invasion (Table III) (Bradbury, 2015), although other authors reported significant correlation of parametrial involvement with disease-free and overall survival (Jiamset, 2016 (Mao, 2016). Current literature suggests that patients with low-risk early-stage CC may be candidates for more conservative approaches, preserving reproductive function (Baiocchi, 2017;Willows, 2016). In contrast, CCRT is the standard of care in locally advanced stages of CC, which exceed the limit of the cervix towards parametria, annexes or pelvic organs (FIGO stages IB2, IIA2-IV) (Meng, 2016).…”
Section: Discussionsupporting
confidence: 79%
“…In agreement with Bradbury et al we found significant correlation of OS with lymph node metastasis but not extrauterine invasion (Table III) (Bradbury, 2015), although other authors reported significant correlation of parametrial involvement with disease-free and overall survival (Jiamset, 2016 (Mao, 2016). Current literature suggests that patients with low-risk early-stage CC may be candidates for more conservative approaches, preserving reproductive function (Baiocchi, 2017;Willows, 2016). In contrast, CCRT is the standard of care in locally advanced stages of CC, which exceed the limit of the cervix towards parametria, annexes or pelvic organs (FIGO stages IB2, IIA2-IV) (Meng, 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the concept of draining the uterus through the ovarian vessels is not new. Following the development of the abdominal radical trachelectomy more than two decades previously, more than 400 infants have since been born in women who have undergone the procedure, proving that uteri remain viable when drained by the ovarian vessels alone …”
Section: Surgical Techniquementioning
confidence: 99%
“…The current study provides the most accurate evidence to inform this subgroup of women with respect to their obstetric outcomes. As management standardization for these women fortunate enough to undergo fertility preservation is desirable, 46 our study can be informative toward treatment individualization. This strategy will need multicenter cooperation to confirm oncological safety.…”
Section: Discussionmentioning
confidence: 99%